2011
DOI: 10.1186/1475-9276-10-10
|View full text |Cite
|
Sign up to set email alerts
|

Equalisation of alcohol participation among socioeconomic groups over time: an analysis based on the total differential approach and longitudinal data from Sweden

Abstract: BackgroundHealth inequality and its social determinants are well-studied, but the determinants of inequality of alcohol consumption are less well-investigated.MethodsThe total differential approach of decomposition of changes in the concentration index of the probability of participation in alcohol consumption was applied to 8-year longitudinal data for Swedish women aged 28-76 in 1988/89.ResultsAlcohol consumption showed a pro-rich inequality, with income being a strong contributor. Overall participation rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 37 publications
5
34
3
Order By: Relevance
“…However, the demand for intensity by binge drinkers is negatively associated with education and income. Given that binge drinkers who drink most intensely are the individuals who will have the worse wider health outcomes, the findings of this paper suggest it is in fact individuals with low education and low income levels who drink more intensely that should be the focus of policy, contrary to Combes et al [20]. In fact, a newly designed randomized trial in the UK [21] is focusing exactly on this group, highlighting how the results presented here could help focus policy interventions.…”
Section: Discussioncontrasting
confidence: 67%
“…However, the demand for intensity by binge drinkers is negatively associated with education and income. Given that binge drinkers who drink most intensely are the individuals who will have the worse wider health outcomes, the findings of this paper suggest it is in fact individuals with low education and low income levels who drink more intensely that should be the focus of policy, contrary to Combes et al [20]. In fact, a newly designed randomized trial in the UK [21] is focusing exactly on this group, highlighting how the results presented here could help focus policy interventions.…”
Section: Discussioncontrasting
confidence: 67%
“…19 Decomposability of CI has led to its broad adoption as a reliable health inequality measure instead of other dispersion measures such as rate ratio. 33,34 The CI is calculated as twice the (weighted) covariance of a health variable and a relative economic rank variable, 34 as follows: …”
Section: Methodsmentioning
confidence: 99%
“…This type of decomposition is based on an approximation of the variation in inequality and is accurate for small changes. Combes et al, 33 in 2011 did a sensitivity analysis using Oaxaca decomposition and TDA separately and suggested that interpretations of Oaxaca method are similar to the TDA results. The third limitation was time inconsistency, ie, death of neonates occurred years before DHS, but the households’ economic status was only measured for the year of DHS.…”
Section: Strengths and Limitationsmentioning
confidence: 96%
“…In tropical regions, the excess in mortality during the low temperature season is particularly counterintuitive as temperatures remain rather high during the so-called winter season and are often perceived as rather agreeable. Nevertheless, several studies have highlighted the association between low temperatures and increased mortality in areas such as Bangladesh, Burkina Faso, Kuwait or Brazil (Burkart et al 2011a; Douglas et al 1991; McMichael et al 2008). Even though monthly mean temperatures do not fall below 18 °C in December and January, the terms winter and cold season are usually applied.…”
Section: Introductionmentioning
confidence: 99%
“…So far, several studies have assessed bioclimatological and temperature-related effects on mortality in Bangladesh (Burkart et al 2011b; Burkart et al 2011a). Special attention in these studies was given to heat effects and summer excess mortality, while excess mortality due to low temperatures and during the cold season is largely understudied.…”
Section: Introductionmentioning
confidence: 99%